Prognostic Models of Primary Sclerosing Cholangitis - A. I. Dolgushina; A. A. Selyanina; V. V. Dubrovina; G. A. Isyangildina; E. R. Olevskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to study the significance of prognostic scales in a target group of patients with primary sclerosing cholangitis (PSC) living in the Chelyabinsk region.Materials and methods. The study included 21 patients with a confirmed diagnosis of primary sclerosing cholangitis (PSC) and a disease duration of at least two years. The primary endpoint studied was death. The MELD, Mayo Risk Score, Amsterdam-Oxford PSC Score, PREsTo score, and UK-PSC Score scales were calculated based on the medical records. Statistical processing was carried out using the SPSS Statistics v.22 application.Results. A retrospective assessment of the risk of mortality using the MELD, Mayo Risk Score and Amsterdam-Oxford PSC Score did not reveal a statistically significant difference between deceased and surviving patients. The UK-PSC Score scale showed the highest predictive value (p = 0.046).Conclusion. The new predictive model UK-PSC Score showed advantages in predicting death in PSC patients compared to other scales.